Comparative Analysis for The Multi Period Degree Minimum Spanning Tree Problem - . Wamiliana; . Amanto; Mustofa Usman (Bandar Lampung University (UBL), 2013)
The Multi Period Degree Constrained Minimum Spanning Tree ProblemÂ (MPDCMST) concerns of finding the total minimum cost of networks installation, where theÂ installation process is divided into some periods. In the beginning of installation process, thecenter of the networks already set (as server, reservoir, etc). The installation process isÂ divided into some period due to some factors, usually fund limitation. During the installationÂ process, the networks is supposed to be maintained its reliability by restrict the numbers ofÂ links that can be connected to the node that already in the networks. In this paper we willÂ discuss and improve the performance of WADR1 and WADR2 algorithms by setting theÂ number of elements in the set of vertices that must be in installed in a certain period as a fixÂ number and adding the length of the path in DFS. The result shows that the modificationsÂ works better.